Interactions of antisense DNA oligonucleotide analogs with phospholipid membranes (liposomes). - Akhtar, S (1991)
Antisense oligonucleotides have the ability to inhibit individual gene expression in the potential treatment of cancer and viral diseases. However, the mechanism by which many oligonucleotide analogs enter cells to exert the desired effects is unknown. In this study, we have used phospholipid model membranes (liposomes) to examine further the mechanisms by which oligonucleotide analogs cross biological membranes. Permeation characteristics of 32P or fluorescent labelled methylphosphonate (MP-oligo), phosphorothioate (S-oligo), alternating methylphosphonate-phosphodiester (Alt-MP) and unmodified phosphodiester (D-oligo) oligodeoxynucleotides were studied using liposomal membranes. Efflux rates (t1/2 values) at 37 degrees C for oligonucleotides entrapped within liposomes ranged from 7-10 days for D-, S- and Alt-MP-oligos to about 4 days for MP-oligos. This suggests that cellular uptake of oligonucleotides by passive diffusion may be an unlikely mechanism, even for the more hydrophobic MP-oligos, as biological effects are observed over much shorter time periods. We also present data that suggest oligonucleotides are unlikely to traverse phospholipid bilayers by membrane destabilization. We show further that MP-oligos exhibit saturable binding (adsorption) to liposomal membranes with a dissociation constant (Kd) of around 20nM. Binding appears to be a simple interaction in which one molecule of oligonucleotide attaches to a single lipid site. In addition, we present water-octanol partition coefficient data which shows that uncharged 12-15 mer MP-oligos are 20-40 times more soluble in water than octanol; the low organic solubility is consistent with the slow permeation of MP-oligos across liposome membranes. These results are thought to have important implications for both the cellular transport and liposomal delivery of modified oligonucleotides.